REGULATION OF SHIFT WORK TO AVOID SHACK OUT OF EMPLOYEES IN HOTEL. - Sutjana, D.P. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 1 Maret 2008)
Since the tragedy of bomb blast at Legian Kuta and SARS epidemictogether with travel warning from foreign country resulting a stepdecreasng of tourist visit to Bali. The Decreasing number of touristvisit cause of tourism stake holders facing many problem such as: emtyroom of hotel, restaurant, travel bureau, small scakle industries. Manyof them close their activities and sack out their employees. But sometwo star hotel in Sanur treid to manage their own way inorder toregulate their employees jog to maintain hotel operational without sackout their employees. The study has been done to find out how to manageemployees shift work in those hotel. The result shown of those 4 hotelat Sanur: 1) one of them gave the employees for 15 days work and 15 daysoff with 50% salary, 2) the second hotel gave one week of and three weekwark with 30% salary off, 3) the third full work, salary as usual butemployees take over hotel renovation job, 4)the employees work as usualwith full salary but laundry work take over by employees themselves.With those management system the hotel operational cost can be minimizedso the dayly operation can be maintain with out shack out theiremployees.
Keywords: shift work, hotel operation, shack out.